Surface modification of polyamide ultrafiltration membrane by plasma polymerisation of acrylic acid - A. Suhaimi,; Mahmoudi, Ebrahim; Siow, Kim Shyong; Mohd Farhanulhakim Mohd Razip Wee, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Increase in hydrophilicity of the filtration membrane could attribute to the fouling reduction and overall filtration performance. In this study, we employ a surface modification on polyamide (PA) membrane by using plasma polymerization with acrylic acid as the precursor by varying the deposition time from 1 to 10 min to induce hydrophilic surface of the membrane without changing the bulk properties of PA membrane. Cross-flow filtration of humic acid using the modified PA membrane was conducted to measure permeates flux and rejection. We calculate the fouling tendencies of each membrane and the result indicates the best performance from sample with 7 min deposition time in terms of permeate flux, rejection and the lowest fouling tendencies. Therefore, this proposed technique could be useful to further improve the commercial filtration membrane; without changing the membrane fabrication process.